Effects of Nitrate Intake on Myocardial Ischemia-Reperfusion Injury in Diabetic Rats - Jeddi,Sajad (2016)
Abstract Background: Coronary artery disease is 2-3 times more common in diabetic individuals. Dietary nitrate/nitrite has beneficial effects in both diabetes and cardiovascular disease. It also has protective effects against myocardial ischemia-reperfusion (IR) injury in healthy animals. However, the effects of nitrate on myocardial IR injury in diabetic rats have not yet been investigated. Objective: We examined the effects of dietary nitrate on myocardial IR injury in streptozotocin-nicotinamide-induced diabetic rats. Method: Rats were divided into four groups (n=7 in each group): control, control+nitrate, diabetes, and diabetes+nitrate. Type 2 diabetes was induced by injection of streptozotocin and nicotinamide. Nitrate (sodium nitrate) was added to drinking water (100 mg/L) for 2 months. The hearts were perfused in a Langendorff apparatus at 2 months and assessed before (baseline) and after myocardial IR for the following parameters: left ventricular developed pressure (LVDP), minimum and maximum rates of pressure change in the left ventricle (±dP/dt), endothelial nitric oxide (NO) synthase (eNOS) and inducible NO synthase (iNOS) mRNA expression, and levels of malondialdehyde (MDA) and NO metabolites (NOx). Results: Recovery of LVDP and ±dP/dt was lower in diabetic rats versus controls, but almost normalized after nitrate intake. Diabetic rats had lower eNOS and higher iNOS expression both at baseline and after IR, and dietary nitrate restored these parameters to normal values after IR. Compared with controls, heart NOx level was lower in diabetic rats at baseline but was higher after IR. Diabetic rats had higher MDA levels both at baseline and after IR, which along with heart NOx levels decreased following nitrate intake. Conclusion: Dietary nitrate in diabetic rats provides cardioprotection against IR injury by regulating eNOS and iNOS expression and inhibiting lipid peroxidation in the heart.